Application of simulation modeling for assessment of environmental safety of soils - Bojko, Tetyana; Skladannyy, Denys; Zaporozhets, Julia; Plashykhin, Sergii (Technology audit and production reserves, 2019)
The object of research is the ecological safety of soil pollution by an industrial enterprise. The general geofiltration process could be considered as a complex of individual physical and physico-chemical processes. During the study, the individual components of the geofiltration process were considered and a reasonable choice of mathematical models for their description is made. One of the problems is the soil type influence assessment and the corresponding geofiltration scheme on the overall filtration processes results. The classification of soils according to the filtration processes that occur in them is considered. For different soils types, influence coefficients of individual processes constituting geofiltration are established. As an assessment of the results of geofiltration, the ratio of the current concentration of the pollutant to its background concentration is proposed. A technique is proposed for determining indicators of purification efficiency, based on a simulation experiment. An algorithm for conducting a simulation experiment on a complex of models was developed taking into account the established coefficients and 10,000 of its implementations were carried out. Based on the simulation experiment results, the values that allow assessing the geofiltration quality is determined: – purification degree interval assessment – soil layer height, which provides the maximum possible purification degree and the complete purification probability when the pollutant passing through the soil layer for all the examined soils. Considering the risk of contaminant entering groundwater through the soil layer is proposed and the assessing scale for this risk based on Harrington desirability scale is established. For all considered soils types, the risk of pollution penetration in cases when the initial concentration of the pollutant exceeds the background by three, five and ten times is assessed. It makes possible to obtain values of geofiltration performance indicators depending on the pollutant initial concentration, taking into account the soil type. This indicators is recommended to take into account for designing locations for potentially hazardous facilities and industries.